A Late Bronze Age Grave from Stara Teskera (Ljubuški) (Archaeologia Adriatica, 2017)
Results of the rescue archaeological excavations from the settlement of Stara Teskera near Ljubuški complement scarce reliable information referring to the Late Bronze Age not only in the region of western Herzegovina but also in the wider cultural region. Spiral-spectacle pendant with tubular central part definitely represents the most interesting find as one of the imposing phenomena of the time.
Keywords: Late Bronze Age; spiral-specacle pendant with tubular central part; Stara Teskera; Ljubuški; western Herzegovina